The Role Of Local Media In Shaping Political Awareness Of University Youth )Field Study On Graduate Students At Tishreen University) (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The problem of the study centered on the following main question: The limited role of the local media in shaping the political awareness of graduate students at Tishreen University? The study also aimed to: Determine the degree of interest of Tishreen University graduate students in the local media, Identify the role of cognitive development by local media, Demonstrate the impact of local media on the electoral participation of graduate students, To reach some results that, if applied, could contribute to the development of the local media and its role in developing the political awareness of university students. The descriptive analytical approach was followed.  Data were collected by distributing a questionnaire to a simple random sample (375) of graduate students at Tishreen University. The data was entered and analyzed by the SPSS program.The main findings of the study were: The local media should not be considered the main source of information for the study sample of graduate students at Tishreen University. The lack of impact of the local media in the development of political knowledge for graduate students at Tishreen University, The limited impact of the local media on the decisions of graduate students in the process of electoral participation, The limited impact of local media in developing political awareness for graduate students at Tishreen University.